CONTENT CREATORS’ BELIEF SYSTEMS AND THEIR SOCIAL MEDIA ECOSYSTEMS - Jaramillo-Dent, Daniela; Latzer, Mchael (AoIR Selected Papers of Internet Research, 2026)
Content creators have become essential players and disruptors in social media ecosystems and society at large. By examining how content creators make sense of these ecosystems, this article offers a conceptual and analytical framework that broadens the scope of existing analyses of creators’ content strategies and activities. Using cognitive, behavioral, and experiential factors, we investigate the belief systems of creators. Creators’ belief systems are examined in relation to different facets of social media ecosystems, representing both mundane and supernatural sense-making approaches. We illustrate how different belief systems affect the choices made by content creators and impact the ecosystem as a whole. Our paper contributes to the field of creator research in three ways: we sketch and conceptualize the social media ecosystem to examine content creators (Figure 1); we propose a visual mapping methodological approach drawing from critical cartography studies and cognitive mapping to explore creators’ beliefs about the different elements of this ecosystem; we provide an analytical proposal that considers the potential for mundane and supernatural beliefs among creators within their social media ecosystems.